2017
DOI: 10.1007/s11655-017-2775-3
|View full text |Cite
|
Sign up to set email alerts
|

Scutellaria barbata D. Don inhibits colorectal cancer growth via suppression of Wnt/β-catenin signaling pathway

Abstract: EESB significantly reduced tumor growth in CRC xenografts mice, and inhibited the viability and survival of HT-29 cells. EESB could suppress the activation of the Wnt/β-catenin pathway, which might be one of the mechanisms whereby Scutellaria barbata D. Don exerts its anticancer activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…More importantly, this compound has shown potent inhibitory effects on tumor growth in mice bearing HCT116 xenograft tumors, without causing significant changes in the average body weights of mice ( Ye et al., 2019 ). Wei et al have found that ethanol extract of Scutellaria barbata D. Don (EESB) inhibits the viability and proliferation of colon cancer HT-29 cells in vitro and suppresses the growth of HT-29 xenograft tumors in vivo ( Wei et al., 2017 ). Mechanism of action studies have indicated that EESB induces β-catenin phosphorylation and reduces the expression level of total β-catenin in HT-29 cells ( Wei et al., 2017 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, this compound has shown potent inhibitory effects on tumor growth in mice bearing HCT116 xenograft tumors, without causing significant changes in the average body weights of mice ( Ye et al., 2019 ). Wei et al have found that ethanol extract of Scutellaria barbata D. Don (EESB) inhibits the viability and proliferation of colon cancer HT-29 cells in vitro and suppresses the growth of HT-29 xenograft tumors in vivo ( Wei et al., 2017 ). Mechanism of action studies have indicated that EESB induces β-catenin phosphorylation and reduces the expression level of total β-catenin in HT-29 cells ( Wei et al., 2017 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
“…Wei et al have found that ethanol extract of Scutellaria barbata D. Don (EESB) inhibits the viability and proliferation of colon cancer HT-29 cells in vitro and suppresses the growth of HT-29 xenograft tumors in vivo ( Wei et al., 2017 ). Mechanism of action studies have indicated that EESB induces β-catenin phosphorylation and reduces the expression level of total β-catenin in HT-29 cells ( Wei et al., 2017 ). However, the active components in EESB that are responsible for EESB-induced β-catenin phosphorylation are yet to be determined.…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
“…SB extract treatment significantly suppressed the activation of several colorectal cancer-related pathways, including STAT3, Erk, and p38 signalings in tumor tissues, and altered the expression of multiple critical target genes such as Bcl-2, Bax, cyclin D1, CDK4, and p21 (Lin et al, 2014). It was also shown that SD inhibited colorectal cancer growth via suppression of Wnt/b-catenin signaling pathway (Wei et al, 2017). HD-SB combination has long been used as a classic herb pair for cancer treatment, and clinical practices show that HD-SB combination exhibits better therapeutic effects than the two single individuals (Yeh et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…This protein is under-expressed in cancer cells and is related to poor clinical outcome through the blockage of apoptosis by caspase inhibition [ 178 ]. Significant reductions of survivin levels were observed for Micromeria fruticosa aerial part extract in MCF-7 and HCT-116 cell lines [ 143 , 144 ], Origanum majorana leaf extract in HT-29 cells [ 171 ], and for Scutellaria barbata whole plant extract in HT-29 cells [ 179 ]. Another key molecule that plays a crucial role in the negative regulation of apoptosis is Her2, belonging to the human epidermal growth factor receptor family.…”
Section: The Lamiaceae Family Plantsmentioning
confidence: 99%
“…CDK/cyclin complexes control Wnt/β-catenin signaling [ 190 ]. Scutellaria barbata extract is related to decreased the expression of β-catenin in HT-29 cells [ 179 ], which is a component of the Wnt/β-catenin signaling pathway responsible for regulating cell growth. The signaling cascade is triggered by binding Wnt ligands to their receptors called Frizzled (Fz) and LDL receptor-related proteins 5 and 6 (LRP5 and LRP6).…”
Section: The Lamiaceae Family Plantsmentioning
confidence: 99%